TGF-β: Many Paths to CD103+ CD8 T Cell Residency - Zhijuan Qiu; Timothy H. Chu; Brian S. Sheridan (Cells, 2021)
CD8 tissue-resident memory T (TRM) cells primarily reside in nonlymphoid tissues without recirculating and provide front-line protective immunity against infections and cancers. CD8 TRM cells can be generally divided into CD69+ CD103− TRM cells (referred to as CD103− TRM cells) and CD69+ CD103+ TRM cells (referred to as CD103+ TRM cells). TGF-β plays a critical role in the development and maintenance of CD103+ CD8 TRM cells. In this review, we summarize the current understanding of tissue-specific activation of TGF-β mediated by integrins and how it contributes to CD103+ CD8 TRM cell development and maintenance. Furthermore, we discuss the underlying mechanisms utilized by TGF-β to regulate the development and maintenance of CD103+ CD8 TRM cells. Overall, this review highlights the importance of TGF-β in regulating this unique subset of memory CD8 T cells that may shed light on improving vaccine design to target this population.